PENGARUH CAPITAL ADEQUACY RATIO, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL, NON PERFORMING LOAN TERHADAP PROFITABILITAS BANK UMUM - Artha, I Made Risky Adhi; Surya Negara Sudirman, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
Banking is a financial institution that has a role in the financial system in Indonesia. The existence of the banking sector has an important role, where in people's lives most of them involve services from the banking sector. The banking sector is currently experiencing a shift in its vital function as an intermediary institution, which should be able to effectively and efficiently allocate its sources of funds to the public. This research was conducted with the aim of knowing the effect of the Capital Adequacy Ratio, Operating Costs on Operating Income, Non-Performing Loans on the Profitability of Commercial Banks listed on the IDX in 2016-2020. The data used in this study is secondary data, namely by looking at the annual financial statements of commercial banks listed on the Indonesia Stock Exchange in 2016-2020 which can be accessed through the website www.idx.co.id. This study uses the method of determining the sample using purposive sampling. The sample used in this study was 145 data on commercial banks listed on the IDX. The analysis technique used is multiple linear regression. The results showed that the Capital Adequacy Ratio (CAR) had a positive effect on profitability in banking sector companies. Operating Expenses Operational Income (BOPO) has a negative effect on profitability in banking sector companies. Non-Performing Loans (NPL) have a negative effect on profitability in banking sector companies.